2021
DOI: 10.1055/s-0041-1731737
|View full text |Cite
|
Sign up to set email alerts
|

Correction of Varus Alignment with Peripheral Osteophyte Removal during Total Knee Arthroplasty: An Assessment with Computer Navigation

Abstract: Techniques for symmetrical balancing in flexion and extension have been described; however, the ideal technique is unclear. This study aimed to clarify whether resection of peripheral osteophytes could restore neutral hip–knee–ankle (HKA) angle of varus deformity of arthritic knees. Data from 90 varus arthritic knees that had undergone total knee arthroplasty (TKA) using a nonimage-based navigation system were analyzed. The change in the coronal mechanical axis, while applying manual valgus stress at extension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In the STRT, the tibial resection plane is soft-tissue-dependent, following resection of the medial osteophytes that affect the preoperative HKAA in a varus knee. Recent studies targeting MA-TKA have reported that removing osteophytes is critical for achieving neutral coronal limb alignment [27,28]. Thus, the removal of osteophytes in the STRT may be the key factor underlying the tremendous effects in cases with severe deformity.…”
Section: Discussionmentioning
confidence: 99%
“…In the STRT, the tibial resection plane is soft-tissue-dependent, following resection of the medial osteophytes that affect the preoperative HKAA in a varus knee. Recent studies targeting MA-TKA have reported that removing osteophytes is critical for achieving neutral coronal limb alignment [27,28]. Thus, the removal of osteophytes in the STRT may be the key factor underlying the tremendous effects in cases with severe deformity.…”
Section: Discussionmentioning
confidence: 99%